Estudo do efeito do resfriamento lento e brusco de argamassa industrializada de assentamento para alvenaria estrutural submetida a altas temperaturas - Coutinho, Ramon Gamalho (2023)
The industrialized bedting mortar for structural masonry has been gaining ground in the civil construction sector as an alternative to the use of mortar prepared in loco and in attention to the mechanical characteristics when linked to structural masonry walls. In this perspective, the aim of this study was to evaluate the effect of slow and abrupt cooling on the mechanical behavior of bedting mortar for structural masonry exposed to high temperatures (300, 600 and 900 °C). In the procedures, obedience to the norms of the Brazilian Association of Technical Norms (ABNT) was adopted as a guiding basis. Industrialized bedting mortar for structural masonry, bagged, with nominal resistance, established by the manufacturer of 4, 12 and 20 MPa was used to carry out the research. Were used cylindrical test specimens (TSs) of 50mm in diameter by 100mm in height, distributed in reference tests, slow cooling tests and abrupt cooling tests, for the ages of 1, 28, and 91 days of post-heating rehydration. Data analyzes regarding compressive strength and static and dynamic modulus of elasticity were performed using the R Core Team (2020) software, as well as the ANOVA statistical tests with Tukey a posteriori, with 5% of significance. Still, the Canonical Correspondence Analysis (CCA) was used. The results that stood out the most showed that regardless of the nominal resistance established by the manufacturer, the cooling method and the rehydration period, the heating temperature of 900°C presented a total or almost total reduction for both analyzed mechanical properties, in addition to the TSs generally degrade soon after cooling. When comparing the nominal strengths, TSs with a nominal strength of 4 MPa, in general, obtained higher results for the static modulus of elasticity, regardless of the cooling method, the rehydration period and the heating temperature. TSs with nominal resistance of 12 and 20 MPa presented higher results for compressive strength. With the exception of TSs with a nominal strength of 20 MPa with 1 day of rehydration, abrupt cooling, heated to a temperature of 300 and 600°C, which showed the best results for the dynamic modulus of elasticity. Given the above, the harmful effect of high temperatures on the mechanical properties of the industrialized laying mortar for structural masonry analyzed in this research is notable, mainly due to the impact arising from the cooling method, as well as the post-heating rehydration period.